Cryptography and coding : 15th IMA International Conference, IMACC 2015, Oxford, UK, December 15-17, 2015 : proceedings /: 15th IMA International Conference, IMACC 2015, Oxford, UK, December 15-17, 2015 : proceedings. ([2015]) - Unknown
No abstract available